2014
DOI: 10.1002/net.21541
|View full text |Cite
|
Sign up to set email alerts
|

A note on shortest path problems with forbidden paths

Abstract: We consider the variant of the shortest path problem in which a given set of paths is forbidden to occur as a subpath in an optimal path. We establish that the most-efficient algorithm for its solution, a dynamic programming algorithm, has polynomial time complexity; it had previously been conjectured that the algorithm has pseudo-polynomial time complexity. Furthermore, we show that this algorithm can be extended, without increasing its time complexity, to handle non elementary forbidden paths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In this situation, we add s as the virtual source point, and s represents the deployment warehouse. 6 as the reserve station. We add t as a virtual point to the network graphics.…”
Section: Model Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this situation, we add s as the virtual source point, and s represents the deployment warehouse. 6 as the reserve station. We add t as a virtual point to the network graphics.…”
Section: Model Solutionmentioning
confidence: 99%
“…[5] tried to find an answer to the question of which shortest path algorithm for the one-to-one shortest path problem ran fastest on a large real-road network and solved the key problem of the computation of shortest paths between different locations on a road network, which appeared in many applications. [6] considered the variant of the shortest path problem in which a given set of paths was forbidden to occur as a subpath in an optimal path, established that the most-efficient algorithm for its solution, a dynamic programming algorithm, had polynomial time complexity, and showed that this algorithm could be extended, without increasing its time complexity, to handle non elementary forbidden paths. [7] investigated the time-dependent reliable shortest path problem, which was commonly encountered in congested urban road networks.…”
Section: Introductionmentioning
confidence: 99%